Environmental Literacy of Islamic Boarding School Students: Study in MA Bilingual-Sidoarjo, East Java, Indonesia - Husamah, H.; Miharja, Fuad Jaya; Hidayati, Dewi Arif (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2020)
Environmental literacy (EL) must be implanted in education, including at the Islamic Boarding School. This study aimed to analyze the EL of students (focus on ecological knowledge/EK, verbal commitment/VC, and actual commitment/AC) in MA Bilingual-Sidoarjo. The approach used was a quantitative approach, supported by qualitative data. This research was ex-post facto, for three months. The research subjects were 120 students (40 each grade), taken by purposive sampling. EL was assessed using MSELS/I. The analysis was carried out by tabulating it into Microsoft Excel 2010. The results showed various EL scores. The aspects of EK vary, from sufficient to high levels. Students in class XI and XII-IPA have a relatively high EK score, while students of class X-IPS have low score. The distribution of students' EK scores in one class group was very diverse. Students tend to have an attitude (VK) that agrees to take pro-environmental actions, especially on small things, but the opposite in terms related to the system and the involvement of many people. At the level of behavior (AC), students tend to show pro-environmental actions. Thus it can be concluded that EL students tend to be diverse, tend to increase their quality according to class level.